Assessment of the mining potential of the public sector of the coal industry of Ukraine - Makarov V.M. (General Energy Institute of the National Academy of Sciences of Ukraine, 2021)
The state-owned coal industry in Ukraine today is in an extremely critical state, both technically, economically and socially. The main factor difficulting and hindering the development of the industry is the insufficient amount of funds for the technical re-equipment of the industry, which today does not make it possible to ensure the advance commissioning of production facilities.Under these conditions, it is relevant to determine the potential of state-owned mines in Ukraine for coal production in the context of reforming the coal industry.Boosting the enterprises of the industry to the level of profitability requires the implementation of a number of measures for the reconstruction and modernization of state-owned enterprises of the mine fund, which are currently located in the territory controlled by the Ukrainian authorities.To determine the technological and economic criteria for the implementation of efficient coal mining technologies in Ukraine, a list of state mines that need modernization has been determined, which includes state mines located in the territory controlled by the Ukrainian authorities and the Dobropolyeugol mine, which were returned from the lease of DTEK to state management.With the use of an improved mathematical model for optimizing the technological development of the coal industry, effective technologies and optimal equipment of treatment complexes for the re-equipment of state mines have been determined, provided that they reach maximum production volumes.As a result of the introduction of advanced technologies for coal mining at the state mines of Ukraine, it is possible to close 8 unprofitable mines, while the volume of production will triple, the ash content of the mined coal will decrease by 6%, the cost of 1 ton of finished coal products will decrease by 2.2 times.The projected structure of the public sector of the coal industry in the territory controlled by the Ukrainian authorities for the period up to 2050 has been developed, according to which the maximum coal production of 23.5 million tons will be achieved in 2035.